Ductile fracture strain in uniaxial tensile test of plane specimen’s - Mohamed Zulqarnain, Mohamed Akram (2012)
This project was performed to determine the ductile fracture strain in uniaxial tensile test of plane specimen. In this project, uniaxial tensile test was performed for three difference material that is aluminum, brass and mild steel. The objective of the test is to identify the value of uniaxial fracture strain for these three difference materials. The specimens have been divided into three difference area: L, P-lateral and S-middle zones. The zones are measured using optical microscope before and after the tensile test to determine the value of ductile fracture strain at those zones. However, the result from tensile test gives an average value of ductile fracture strain. The second step was to determine the suitable point or area to get the accurate uniaxial ductile fracture strain. The element of the material with stress triaxiality,k = 0.33 is the location where the uniaxial fracture strain was occurred. Finite element analysis using MSC Patran/Marc 2008r1 software was used to determine the element with stress triaxiality,k = 0.33. In MSC Patran software, the specimen was divided into several nodes to represent the study location for lateral and middle zones. In this project, the model was divided into eleven points. Each point has differences values of stress triaxiality after ultimate tensile strength occurred. The finite element analysis data of engineering stress-strain curve was compared with experiment engineering stress-strain curve in order to determine the fracture point of the model. The state of stress for each material was determined in order to get the uniaxial ductile fracture strain nodes. The result shows that uniaxial ductile fracture strain occurred at nodes 2577 for aluminium and brass, while uniaxial ductile fracture strain for mild steel occurred at node 2598. It is also shown that the fracture strain at L and P-lateral zones was the nearest to the uniaxial ductile fracture strain.